Some Psychopolitical and Social Psychohistorical Processes in the Formation of Classical Period Ottoman Identity - Hadiye Yılmaz Odabaşı; Deniz Ülke Arıboğan (Siyasal: Journal of Political Sciences)
Traditional disputes on pre-modern Ottoman identity mostly revolve around the topic of “Is there a single Ottoman identity or various Ottoman identities?” Some researchers point out that the name “Ottoman” refers to the ruling class. On the other hand, some researchers mention a supra-religious and supra-ethnic unionist consciousness and the existence of an Ottoman identity as an umbrella of sovereignty. The basic argument of this paper is that the Ottoman Empire’s institutional structure and organization, which governed the group members’ contacts and connections in political, economic, cultural, and social life, provides a good setting for the formation of the dual identity paradigm. In the two big spaces of social life in the Ottoman society, commercial and agricultural life, social life organized by the waqf system from places of worship to educational institutions, and daily life and practices became collectivized to a large extent by preserving religious and ethnic sub-identities via common spaces such as bazaars and squares. Thus, these patterns established through social structures/relationship networks made it possible for the multi-characterized Ottoman subjects to socialize and to build a collective Ottoman upper identity. Objective representations such as the Ottoman Greek, the Ottoman Armenian, and the Ottoman Jew can be read as the most concrete indicators of dual identity formations in the Ottoman large group.